2019
DOI: 10.1002/lary.27791
|View full text |Cite
|
Sign up to set email alerts
|

Chronic opioid use in patients undergoing treatment for oropharyngeal cancer

Abstract: Objectives/Hypothesis Head and neck cancer pain is a prevalent problem, and the current opioid crisis has highlighted concerns raised in chronic pain management. This study assessed the characteristics of opioid use in patients undergoing treatment for oropharynx cancer and identified risk factors associated with chronic opioid use. Study Design Retrospective cohort study. Methods A study was conducted of 198 eligible patients who underwent radiotherapy as part of their treatment for oropharynx cancer at a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 25 publications
(49 reference statements)
3
28
3
Order By: Relevance
“…Age was among the most significant factors influencing patients’ postoperative pain experience and risk of continued opioid use in this study. The association of younger age with higher prevalence of chronic opioid use has also been reported among oropharynx and oral cavity cancer patients treated with any modality, including surgery . The impact of age on pain and opioid use has not previously been well described among patients undergoing major head and neck reconstructive surgery but is highly relevant to clinical practice for several reasons.…”
Section: Discussionmentioning
confidence: 98%
“…Age was among the most significant factors influencing patients’ postoperative pain experience and risk of continued opioid use in this study. The association of younger age with higher prevalence of chronic opioid use has also been reported among oropharynx and oral cavity cancer patients treated with any modality, including surgery . The impact of age on pain and opioid use has not previously been well described among patients undergoing major head and neck reconstructive surgery but is highly relevant to clinical practice for several reasons.…”
Section: Discussionmentioning
confidence: 98%
“…A total of 134 studies were identified, with 7 retrospective studies [8][9][10][11][12][13][14] (32.3%) underwent surgery followed by adjuvant RT/CRT ( Table 1).…”
Section: J O U R N a L P R E -P R O O F Resultsmentioning
confidence: 99%
“…Significant heterogeneity is noted between studies and is accounted for, in part, by the random effects model. Only two studies included demographic patient data on chronic pain 12,13 which was insufficient for pooling in a meta-analysis.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…41 Opioids are among the most widely used drugs for cancer patients with acute and chronic pain, as well as during the perioperative period, 41 and over 50% of HNSCC patients require opioids for pain control. 42,43 The growing understanding regarding the role opioids play in the development of some cancer types, including SG-SCC carcinoma, raises the question of opioid safety in cancer pain management. Over the past decade, there has been evolving literature suggesting a relationship between opioids and cancer progression and recurrence.…”
Section: Discussionmentioning
confidence: 99%